ChemInform Abstract: Selective C—Si Bond Formation Through C—H Functionalization. Issue 41 (October 2015) - Sharma, Ritika; Kumar, Rakesh; Kumar, Inder; Singh, Bikram; Sharma, Upendra
Abstract Review: [59 refs.